Collagenated Porcine Heterologous Bone Grafts: Histomorphometric Evaluation of Bone Formation Using Different Physical Forms in a Rabbit Cancellous Bone Model - Falacho, Rui I. (2021)
Collagenated porcine-derived bone graft materials exhibit osteoconductive properties and the development of different formulations intends to enhance bone regeneration. This study aims to evaluate bone healing in a rabbit cancellous bone defect in response to grafting with different physicochemical forms of heterologous porcine bone. Twenty-six adult male New Zealand White rabbits received two critical size femoral bone defects per animal (n = 52), each randomly assigned to one of the five tested materials (Apatos, Gen-Os, mp3, Putty, and Gel 40). Animals were sacrificed at 15- and 30-days post-surgery. Qualitative and quantitative (new bone, particle and connective tissue percentages) histological analyses were performed. Histomorphometry showed statistically significant differences in all evaluated parameters between mp3 and both Putty and Gel 40 groups, regardless of the timepoint (p < 0.05). Moreover, statistical differences were observed between Apatos and both Putty (p = 0.014) and Gel 40 (p = 0.007) groups, at 30 days, in regard to particle percentage. Within each group, regarding new bone formation, mp3 showed significant differences (p = 0.028) between 15 (40.93 ± 3.49%) and 30 (52.49 ± 11.04%) days. Additionally, intragroup analysis concerning the percentage of particles revealed a significant reduction in particle occupied area from 15 to 30 days in mp3 and Gen-Os groups (p = 0.009). All mp3, Gen-Os and Apatos exhibited promising results in terms of new bone formation, thus presenting suitable alternatives to be used in bone regeneration.